Phase Change Material on Augmentation of Fresh Water Production Using Pyramid Solar Still - S. Ravishankara; P.K. Nagarajan; D. Vijayakumar; M.K. Jawahar (International Journal of Renewable Energy Development, 2013)
The augmentation of fresh water and increase in the solar still efficiency of a triangular pyramid is added with phase change material (PCM) on the basin. Experimental studies were conducted and the effects of production of fresh water with and without PCM were investigated. Using paraffin as the PCM material, performance of the solar still were conducted on a hot, humid climate of Chennai (13°5′ 2" North, 80°16′ 12"East), India. The use of paraffin wax increases the latent heat storage so that the energy is stored in the PCM and in the absence of solar radiation it rejects its stored heat into the basin for further evaporation of water from the basin. Temperatures of water, Tw, Temperature of phase change material, TPCM, Temperature of cover, Tc were measured using thermocouple. Results show that there is an increase of maximum 20%, in productivity of fresh water with PCM.